The Transformation of Religious Moderation in the Islamic Religious Education Curriculum - Rahman, Abdul; Hendri, Novi; Adawiyah, Rabiatul; Dina, Hidayatul; Faizul, Faizul (El-Rusyd, 2026)
Religious moderation has become a crucial discourse in Indonesian Islamic education amid rising radicalism, intolerance, and identity polarization. This study focuses on how religious moderation is organically practiced in a multireligious educational setting. The study employs a qualitative case study design at Madrasah Tsanawiyah Negeri 1 Kepulauan Meranti, Riau, utilizing document analysis, participant observation, and in-depth interviews with 15 informants. Data were analyzed through the stages of thematic reduction, display, and verification following Miles and Huberman. The findings indicate that religious moderation cannot be reduced to state policy alone but must emerge as a theological consciousness rooted in the Islamic value of wasathiyah. The study concludes that a holistic-integrative transformation of the Islamic Religious Education curriculum encompassing content, methods, activities, and character assessment is absolutely necessary to foster a generation that is moderate, tolerant, and committed to national unity. The case of State Madrasah Tsanawiyah 1 in the Meranti Islands, Riau, demonstrates that the coexistence of Islamic madrasahs and Buddhist educational institutions can serve as a living laboratory for religious moderation education, evidenced by organic interfaith cooperation that transcends formal policy mandates.